Sfaxitude: History, Collective Memory, and the Diaspora of the Descendants of Sfax (جماعة, 2020)
This article examines Sfaxitude: the entirety of the connections, feelings, and longings of Jews, Muslims, and Christians for their colonial-period life in Sfax, their city of origin in Tunisia. Sfaxitude encompasses a complex of previously formed identities, which continued to shape the minds and lives of the people who migrated from Sfax and the lives they created in the post-colonial era. The article elaborates on a number of figures originating from Sfax, in particular Marcel Mahmoud Reggui. Reggui, a Muslim who converted to Christianity, has been a key figure in the formation of the Sfaxian diasporic community since his publication of the yearbook La Diaspora Sfaxienne in 1967, consolidating the community around it in the process. The article proposes that Reggui be seen as an “identity broker”, thanks to his actions linking the various groups that emerged from Sfax. The case discussed in the article enables closer examination of the stages in the construction of a diaspora: life in Sfax during the colonial period; immigration to France, Israel, and other places; ongoing contact with the city; the construction of means of communication between the various diasporic outposts of the community; and the processes of preserving the links and contents of a collective memory. Beyond that, the case of Sfaxitude is special in the sense of vocation held by many of its members: a sense transmitted through a universal message of brotherhood and tolerance between human beings, underpinned by their life experiences in Sfax and the diaspora.